2019
DOI: 10.3390/e21080730
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry Properties of Mixed and Heat Photo-Assisted Noise in the Quantum Hall Regime

Abstract: We investigate the photo-assisted charge-heat mixed noise and the heat noise generated by periodic drives in Quantum Hall states belonging to the Laughlin sequence. Fluctuations of the charge and heat currents are due to weak backscattering induced in a quantum point contact geometry and are evaluated at the lowest order in the tunneling amplitude. Focusing on the cases of a cosine and Lorentzian periodic drive, we show that the different symmetries of the photo-assisted tunneling amplitudes strongly affect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…In the cosine case for a non-zero θ (right panel of Figure ( 3)), it is evident the almost total suppression of the squeezing because the minimum of the quadrature A 2 0 ( A 2 π ) is only slightly below the quantum vacuum (horizontal gray dashed line) while the other stays well above. Concerning Figure 3, the symmetry between the two quadratures for (q → −q), observed in the non-interacting case [31], is still preserved in the interacting one according to the general properties of the photo-assisted amplitudes [64,65]. When we turn our attention to the Lorentzian case, in Figure 4, the situation appears quite different.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In the cosine case for a non-zero θ (right panel of Figure ( 3)), it is evident the almost total suppression of the squeezing because the minimum of the quadrature A 2 0 ( A 2 π ) is only slightly below the quantum vacuum (horizontal gray dashed line) while the other stays well above. Concerning Figure 3, the symmetry between the two quadratures for (q → −q), observed in the non-interacting case [31], is still preserved in the interacting one according to the general properties of the photo-assisted amplitudes [64,65]. When we turn our attention to the Lorentzian case, in Figure 4, the situation appears quite different.…”
Section: Resultsmentioning
confidence: 92%
“…When we turn our attention to the Lorentzian case, in Figure 4, the situation appears quite different. First of all, the mirror symmetry encountered for the cosine drive is absent here [64,65]. Then, the interactions still increase the values of the quadratures' minima but A 2 π , for q = 1, continues to stay well below the quantum vacuum limit.…”
Section: Resultsmentioning
confidence: 96%
“…Coefficients in Eq. ( 19) represent the probability amplitude for electrons to absorb (l > 0) or emit (l < 0) a photon at energy ω and, for this reason, are called photo-assisted coefficient [3,110,111]. By defining the following fermionic annihilation operator…”
Section: A Solution Without Proximity Effectmentioning
confidence: 99%
“…In mesoscopic conductors, not only charge, but also heat fluctuations, are significant. This leads to heat and mixed charge-heat correlators, as illustrated by Ronetti et al [ 21 ] for a harmonically driven quantum Hall bar. The system shows quasiparticle excitations of fractional charge (Laughlin states), and it is demonstrated that the mixed noise differs for integer and fractional filling factors.…”
mentioning
confidence: 92%